Development of processed banana packaging for woman’s group of Baan Mae Kurd Luang - พรมมาแบน ศิรินภา; ทองเปรมจิตต์ ศศิธร (RMUTL Journal of Business Administration and Liberal Arts, 2018)
Thai entrepreneurs are lack of knowledge and understanding on the use of packaging materials to suite for marketing and packaging design with local identities to distribute as souvenirs to tourists. This research aims to study product placement and packaging. To design and develop packaging to meet the needs of consumers. And to create an archetype for the group of entrepreneurs to apply. The results of the study found that baked banana with honey and sweet banana crisps, under the brand: Mae La-or, focus on the main target who buy local souvenirs (Niche Market). The researchers therefore took the prominence of local identity i.e. the architectural tourism attraction. The “Mae Sod – Myawadee border gate” is located at the top of the mountain at the border. The identity colour scheme is yellow Champa (Thai flower). There are 2 forms of graphic designs. The evaluating result of the designs from 2 groups of the experts of packaging and entrepreneurs found that both groups figured the 2nd graphic design more than the 1st graphic design. The researchers had adapted them to be the same theme. In terms of material and structure, the Individual Package should use materials that can extend the shelf life and ease of use, as well as the market position. Therefore, the entrepreneur is able to choose plastic bags that depends on the desired shelf life for baked banana with honey and sweet banana crisps as follows: Laminate Type 1 – transparent bags for 3 to 6 months shelf life, Laminate Type 2 – solid bags with aluminium in middle layer for 6 to 12 shelf life and Laminate Type 3 – solid bags with aluminium foil for 12 to 18 months shelf life. The graphic can be printed directly on the bag or printed on a sticker. The baked banana with honey is divided into 10 inner packages. Net weight is 250 grams in the folding carton with gable top. The package is made of Coated Duplex Board and is designed to leave the trace after the first opening (Tamper Evidence). The shopping bag is made of coated paper, 160 – 190 grams.